The Determinants of Islamic Banks’ Stock Prices Volatility: Evidence From the GCC Countries - Muhammad Muhajir Aminy; Ahmad Sauqi (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
Islamic banks’ stock is a new interesting material to be discussed among Islamic economics scholars. The majority of Islamic banks’ stocks presents in middle-east countries, especially those which are joining as the Gulf Cooperation Council (GCC) countries. Samples in this study were 10 islamic banks in the Gulf Cooperation Council (GCC) Countries with secondary data from their financial report. A panel data regression analysis was employed to seek the influence of all observed variables (ROA, ROE, and ICSR (zakat)) as the determinant factors toward Islamic banks’ stock prices volatility. The study found that all the independent variables simultaneously have an impact on Islamic banks’ stock prices in that area. The study also found that the variable of ROA has a negative significant impact and the variable of ROE has a positive significant impact, while total of zakat spending by corporates as the ICSR variable has an insignificant impact on Islamic banks’ stock prices because zakat is an obligation to pay within the GCC countries. This study suggested all Islamic banks globally to consider investors’ sentiment toward Islamic banks’ financial condition before entering the Islamic capital market.